Importance of experimental evaluation of structural parameters for constitutive modelling of aorta - Fischer, Jiří; Turčanová, Michaela; Man, Vojtěch; Hermanová, Markéta; Bednařík, Zdeněk; Burša, Jiří (Journal of the mechanical behavior of biomedical materials, 2023)
The study compares stresses and strains in the aortic wall derived using different constitutive models for various stress-strain conditions. Structure-based constitutive models with two fibre families with (GOH) and without (HGO) dispersion of collagen fibres are compared. The constitutive models were fitted to data from equibiaxial tension tests of two separated layers of the porcine aortic wall. The initial fit was evaluated with unrestricted parameters and subsequently, the mean angles of the fibre families and the angular dispersion were fixed to the values obtained from histology. Surprisingly, none of the tested models was capable to provide a good quality fit with histologically obtained structural parameters. Fitting the HGO model to experimental data resulted in two fibre families under angles close to ±45°, while the GOH model resulted in a nearly isotropic fibre distribution. These results indicate that both of these models suffer from the absence of isotropic strain stiffening. After having modified both models with corresponding additional members based on the Yeoh model of matrix, we obtained a perfect fit to the measured data while keeping the structural histology-based parameters. Finally, significant differences in compliance and resulting stresses and strains between different models are shown by means of simulations of uniaxial tension test, equibiaxial tension tests and inflation of the aorta.
Keywords: Swine; Soft tissue; aorta; Models, Biological; Stress, Mechanical; Polarized light microscopy; Constitutive modelling; Animals; biologické modely; biomechanika; Histogram; Aorta; Fibre direction; Biomechanical Phenomena; zvířata; prasata; Collagen; mechanický stres